2014
DOI: 10.1002/jwmg.749
|View full text |Cite
|
Sign up to set email alerts
|

Survival and productivity of eastern wild turkey females in contrasting landscapes in Wisconsin

Abstract: Eastern wild turkeys (Meleagris gallopavo silvestris) have colonized the entire state of Wisconsin, USA since being successfully reintroduced in the 1970s. Recently, conservation groups have expressed concerns regarding habitat quantity and quality in association with population plateaus and declines in local abundance in some portions of the state. Estimates of survival and productivity are needed to identify the current population status and for drafting effective management plans. We evaluated female easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(73 citation statements)
references
References 30 publications
7
65
1
Order By: Relevance
“…However, we found that the effect of either nest or poult survival on λ was 2.3–3.2 times greater than fall‐winter survival in both landscapes. Fall harvest rates of radio‐marked female turkeys were low (<5%) during our field study (Pollentier et al ) and likely had less influence on survival than harvest rates modeled in other studies (≥10%; Vangilder and Kurzejeski , Alpizar‐Jara et al ).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, we found that the effect of either nest or poult survival on λ was 2.3–3.2 times greater than fall‐winter survival in both landscapes. Fall harvest rates of radio‐marked female turkeys were low (<5%) during our field study (Pollentier et al ) and likely had less influence on survival than harvest rates modeled in other studies (≥10%; Vangilder and Kurzejeski , Alpizar‐Jara et al ).…”
Section: Discussionmentioning
confidence: 55%
“…Apparent nesting and renesting rates are typically biased low, but we used a Horvitz–Thompson estimator (Dinsmore et al ) to account for nests that may have failed before discovery. Disturbance of nesting females was kept to a minimum as we only flushed females once to confirm nesting and determine clutch size; only 4 of 82 (5%) confirmed nesting attempts resulted in abandonment (Pollentier et al ). Our estimates of poult survival may have been biased low, but flush counts were not performed until broods were approximately 14 days of age and we excluded data if a radio‐marked female was lost or died prior to an initial flush count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted our research in 4 separate townships (Fairchild, Hale, Stark, and Westford; 9,300 ha each) within the Central Sand Plains and Western Coulees and Ridges ecological landscapes in southwest and west‐central Wisconsin, USA (Fig. ; Pollentier et al ). We collected data on female turkey habitat selection during 8 April–24 July, 2010–2011, which we defined as spring and corresponded to biological events of turkeys in our study areas (Wright et al , Pollentier et al ).…”
Section: Study Areamentioning
confidence: 99%
“…1; Pollentier et al 2014b). We collected data on female turkey habitat selection during 8 April-24 July, 2010-2011, which we defined as spring and corresponded to biological events of turkeys in our study areas , Pollentier et al 2014b. We categorized study townships based upon dominant, aggregated land cover types within each township.…”
Section: Study Areamentioning
confidence: 99%